Identifying and Evaluating the Effect of Poisonous Plants on Honeybee Colonies in East Amhara, Ethiopia - Lema, Meresa; Tsegaye, Agazhe; Bihonegn, Addisu; Ibrahim1, Yesuf; Desale, Ertiban; Girmay, Ayalew; Tsegaye, Alemu Tsegaye (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The study was conducted to identify and evaluate the effect of poisonous plants on honeybee colonies in Eastern Amhara. Two beekeeping potential zones, South Wollo and Waghimra, were selected purposively. Using a multistage sampling technique, a total of six districts and 18 local kebeles were addressed in this survey. A total of 225 sample beekeepers were selected purposively based on their experience in beekeeping, and data was collected through interviews. The result indicated that about 15.6% of the respondents had awareness about the existence of honeybee poisonous plants in their locality. According to the present finding, a total of 11 plant species were identified as poisonous plants. These include Helianthus anus, Agave spps, Aloea spps, Parthenium hysterophorus, Euphorbia tirucalli, Ranunculus mustifidus, Euphorbia spps, Guizotia scarab, Acacia saligna, Lanthana camara, and Nicotiana glauca. The effect of the poisonous plants might be either direct physical damage to honeybees or causing internal abnormality, which can lead to death. Some plants were repellent and honeybee killers, while others weakened and were responsible for the dwindling of colonies during their flowering period. The other plant species were reported to cause (vomiting, allergic reactions, headaches, diarrhea, and bad taste) to the consumers by irritating consumers' throats. The identified poisonous plant species were located abundantly in the (home garden, fence, and watershed) areas of the study area where apiaries existed. Though these plants had no value to the honeybee, beekeepers did not try to remove the plants from the area where honeybee colonies are available. Moreover, by this survey, the identified poisonous plants may or may not be poisonous plants unless checked by critical investigation of chemical analysis or by feeding of honeybees. Hence, it could be recommended that a detailed chemical analysis of these identified plants should be conducted to devise and implement appropriate control and prevention measures.